Implementação de práticas experimentais sobre os efeitos Seebeck e Peltier em aulas de Física do ensino médio - Silva, Clésio Martins (2017)
The present work aimed at the accomplishment of a series of experimental practices for the verification of the effects Seebeck and Peltier. The project was applied to the class of the third year A of the Alfredo Nasser State College, composed of 15 students, in the city of Britânia - GO. The Seebeck and Peltier effects are thermoelectric effects, that is, effects that deal with the direct conversion of temperature difference to potential difference and vice versa. Despite the richness of physics concepts involved in explaining these effects (ranging from temperature, electric current, potential difference, electrical and thermal conduction to semiconductors) and their importance to science and to technological and industrial applications they are not part of of the high school curriculum. The didactic textbooks also do not address the subject. By inserting in our classes, the thermoelectric effects - with emphasis on experimentation - we aim to promote a curricular update and also an opportunity to implement experimental classes in our teaching practice, considering that in our School there are no physical laboratories. The generated educational product consists of the text Experimental Routings on the Seebeck and Peltier Effects, involving 10 experiments: 04 (four) related to the verification of the Seebeck effect, 04 (four) related to the construction of thermocouples and 02 (two) related to the Peltier effect, one of them being the construction of a mini refrigerator using a Peltier tablet powered by a notebook. As a result of our work, we mention the excellent opportunity to discuss in an integrated way several concepts and magnitudes, which are often approached disconnected from each other, and also to highlight the importance of Physics for technological applications - a relationship that seems obvious, but which, unfortunately, is often not seen by our students. In the student part, we emphasize the experience with the own experimental classes that were new for the absolute majority of the students of the class and the motivation provided by the experimentation that influenced positively in the dynamics of the theoretical classes.